Proton Momentum Distributions and Elastic Electron Scattering form Factors for Some Even-A 1f-2p Shell Nuclei - Abdullah, Ahmed N (Al-Nahrain Journal of Science, 2018)
The proton momentum distributions (PMD) and elastic charge form factors, F(q), of the ground state for some even mass nuclei in the 1f-2p shell, such as 56Fe, 62Ni and 68Zn nuclei have been calculated in the framework of the Coherent Density Fluctuation Model (CDFM) and expressed in terms of the fluctuation function (weight function) (|f(x)|^2 ). The fluctuation function has been related to the charge density distribution (CDD) of the nuclei and obtained from the theory and experiment. The feature of the long-tail behavior at high momentum region of the proton momentum distributions has been determined by both the theoretical and experimental fluctuation functions. The observed electron scattering form factors for 56Fe, 62Ni and 68Zn nuclei are in very good agreement with the present calculations throughout all values of momentum transfer q.